Strategies for Empowering Entrepreneurs to Enhance the Creative Economy in Bandung - Makalalag, Sukiman; Soegoto, Dedi Sulistiyo (Universitas Komputer Indonesia, 2025)
This think about points to distinguish and analyze compelling entrepreneurial strengthening procedures to bolster the development of the inventive economy in Bandung. By actualizing the correct methodologies, it is anticipated that imaginative business people can create, improve, and improve the region's financial competitiveness. This investigate utilizes a case ponder approach by collecting information through interviews, perceptions, and writing thinks about. The consider centers on government arrangements, preparing and hatching programs, get to to capital, and the utilization of advanced innovation within the inventive economy segment. Bandung is known as a center for the inventive economy in Indonesia, with driving segments such as mold, culinary expressions, plan, and computerized innovation. To drive the development of this division, entrepreneurial strengthening techniques are required, counting abilities improvement through preparing and brooding, less demanding get to to capital, commerce biological system reinforcing, and government arrangement support. Case thinks about demonstrate that activities such as the advancement of inventive commerce communities and capital help programs have essentially contributed to the development of the inventive economy in Bandung. The investigate discoveries appear that the execution of legitimate strengthening methodologies can cultivate the development of inventive business people in Bandung. Back from the government, commerce communities, and budgetary teach plays a pivotal part in making a conducive biological system for the advancement of the imaginative economy within the locale.